Binder-free in situ interface reconstruction of NiMoO4 nanorods over Ni(OH)2 nanosheets for efficient urea oxidation - Kumar, Yogesh; Barik, Sidharth; Kharabe, Geeta Pandurang; Torris, Arun; Singh, Mayank U.; Mohan, S.; Galave, Chaitanya; Tekawadia, Jyoti; Kanawade, Rajesh; Kurungot, Sreekumar (Advanced Sustainable Systems, 2025)
Replacing the energy-intensive oxygen evolution reaction (OER) with the urea oxidation reaction (UOR) in electrochemical water splitting offers simultaneous green hydrogen production and urea-rich wastewater oxidation, enhancing energy efficiency and economic viability. In this study, a non-noble metal-based binder-free NiMoO4/Ni(OH)2/NF electrocatalyst is developed, featuring NiMoO4 nanorods anchored on Ni(OH)2 nanosheets. This unique morphology facilitates a highly active in situ reconstructed interface, delivering a current density of 134 mA cm-2 at 1.40 V (vs RHE) in 1 m KOH with 0.33 m urea, significantly outperforming its individual components. The catalyst demonstrates excellent stability over 50 h at 30 mA cm-2. When integrated into an anion exchange membrane urea electrolyser (13 cm2 area) with Pt@C/NF as the HER cathode, the system achieves 192 mA cm-2 at 1.60 V. The post-UOR studies confirm the presence of an amorphous NiMoO4-crystalline Ni(OH)2 interface, which plays a key role in enhancing the availability of the active sites to enhance the UOR performance. The improved electrochemical performance of the engineered catalyst can be ascribed to the in situ reconstructed amorphous-crystalline interface, optimal hydrophilicity, reduced charge transfer resistance, and the distinct morphology. This strategy offers a promising pathway for developing highly active electrocatalysts for energy conversion applications.
Keywords: AEM; electrolyser; OWS; tomography; UOR; wastewater